2021
DOI: 10.1519/jsc.0000000000003160
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Light-Based Electronic Target for Testing Response Time in Fencers

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…In short, the present study used the Stroop test as a suitable tool to create induced mental fatigue that allowed us to recreate the mental state of athletes engaged in competition actions. It is worth noting that in sports characterized by a low RT, such as fencing [ 21 ], table tennis [ 22 ] and shooting [ 23 , 24 , 25 ], players are required to have temporal and spatial precision to be able to hit the primary target: the opponent, ball or an object in flight. The choice to evaluate the effect of mental fatigue allowed us to think about the trade-off that occurs in natural environments in which speed and spatial precision are correlated with the level of skill and RT times are decisive for achieving the optimal result.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the present study used the Stroop test as a suitable tool to create induced mental fatigue that allowed us to recreate the mental state of athletes engaged in competition actions. It is worth noting that in sports characterized by a low RT, such as fencing [ 21 ], table tennis [ 22 ] and shooting [ 23 , 24 , 25 ], players are required to have temporal and spatial precision to be able to hit the primary target: the opponent, ball or an object in flight. The choice to evaluate the effect of mental fatigue allowed us to think about the trade-off that occurs in natural environments in which speed and spatial precision are correlated with the level of skill and RT times are decisive for achieving the optimal result.…”
Section: Discussionmentioning
confidence: 99%
“…The present study sheds new light on the role of feedback for motor learning. Indeed, literature demonstrated that feedback for motor learning can also be effective when performers’ attention is moved away from their body movements (external feedback; Wulf et al, 2002; De Giorgio et al, 2019). Verbal instructions vs. external feedback are two different approaches, each one having its own particularity but the current predominant observation here is that “feedback manipulations” seem to be more effective when it comes to enhancing the learners’ awareness of their body movements (Schmidt, 1991; Schmidt and Lee, 1999; Wulf et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In team sports, scientists have developed a lot of practical and learning techniques to provide educational and academic resources in order to obtain better knowledge among learners (Lauber and Keller, 2014; De Giorgio et al, 2018, 2019; Hraste et al, 2018). Several techniques and tools can be put at the service of sport practice and physical education, especially in motor learning (ML; Schmidt and Lee, 2011; Drost and Todorovich, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fencing requires a high level of physical and cognitive abilities, such as low reaction times, precision, and tactical decision-making (Gutiérrez-Cruz et al 2015;Sorel et al 2019;de Giorgio et al 2021). In fencing, a low reaction time is important for fencers in order to react to the actions of the opponent without being hit.…”
Section: Fencingmentioning
confidence: 99%